(3BOGH GdeQjV hGdJeQjVs - (3GdMSf Hf YR GdOjf Hf GdMSf Hf GdeDjO GdMSfj, CHh eMeO,J (B929 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CMGW HLejY UaGJ GdceGd CdaJ BOGHkG JJYdb HGdeQjV hGdJeQjV hLYdJ eG PcQJg ai Jdc GdBOGH ai KdGKI CHhGH s
(3BNQgG (B:s
(3bGd eDdag (B: (3hbO Je eG CQGOfGg haQZ Qbe eG CdafGg hLeYfGg ef gPg GdhUGFa hGdBOGH ai KdGKI CHhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe (B2 - (3U (B1 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B214s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCeHQhRjGfG (B(d 532 ii) s
Keywords: (3GdWHs